The Effectiveness of Resiliency Training on Academic Stress and Psychological Well-Being - Risky Nurlita Maylinda; Rahmi Lubis; Yudhistira Fauzy Indrawan (Journal of Educational, Health and Community Psychology, 2024)
Divorce transforms an individual into a single parent, prompting them to place their children in Islamic boarding schools for enhanced supervision. The repercussions of divorce on adolescents are substantial, particularly for those in boarding schools. These adolescents often grapple with heightened academic stress, attributable to rigorous learning demands and a lack of parental support, resulting in diminished psychological well-being. This study endeavors to implement resilience training as a pilot intervention, aiming to alleviate academic stress and enhance the psychological well-being of adolescents in boarding schools with divorced parents. The research design adopts a non-randomized pretest-posttest control group format, encompassing 30 adolescents. The evaluation tools employed include the ESSSA educational stress scale for adolescents (16 items), a psychological well-being assessment (42 items), and a resilience measurement (19 items). Utilizing independent t-tests and paired t-tests, the findings indicate a noteworthy reduction in academic stress (p=.000) and a concurrent improvement in psychological well-being (p=.000).